The Role of K+, Ca2+ channels, Some Endothelium Hyperpolarizing Factors in Taurine Induced Vasorelaxation in Rats Aorta - Haji, Abdulsatar A.; Al-Habib, Omar A.M. (Technium BioChemMed, 2021)
The current study included the relaxant effect of taurine on rat’s aortic rings and the mechanism behind this relaxation. Taurine produced a potent spasmolytic effect on aortic rings at concentrations from zero to 80 mM. The results of K+ channel subtypes using specific blockers indicated that the Kv channel has a considerable role in taurine-induced relaxation, while KATP has a limited role, Exposure of aortic rings to combinations of two K+ blockers showed that KCa, Kv, and KIR play important role in taurine mediated relaxation. The endothelium-derived hyperpolarizing factors used showed responses to a variable extent in taurine mediated relaxation; since NO and cGMP played a major role whereas PGS played a minor role in taurine mediated relaxation. Finally, the results also indicated that taurine-mediated relaxation is endothelium-dependent.